School Indiscipline and Crime - Tony Beatton; Michael P. Kidd; Matteo Sandi (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the impact of compulsory schooling on in-school violence using individual-level administrative data matching education and criminal records from Queensland. Exploiting a dropout age reform in 2006, it defines a series of regression-discontinuity specifications. While police records show that property and drug offences decrease, education records indicate that in-school violence increases. Effects concentrate among students with prior criminal records and their classmates, with greater exposure to in-school violence leading to increased criminality at older ages. Dropout age reforms may alter the school environment and prior studies that fail to consider in-school behaviour may over-estimate their short-run crime-reducing impact.
Keywords: I20; K42; 330; youth crime; minimum dropout age; school attendance